The Mood Repair Effect of Positive Involuntary Autobiographical Memory Among Japanese Adults: An Experimental Study. (April 2022) - Hashimoto, Junya; Kanayama, Noriaki; Miyatani, Makoto; Nakao, Takashi
Involuntary autobiographical memories are memories of personal events that come to mind without an intentional attempt at retrieval. Previous studies have shown that positive involuntary autobiographical memory retrieval improves negative mood, known as the mood repair effect, in daily life. However, the cues relating to involuntary autobiographical memories were not controlled in these previous studies, and the mood repair effect has not been shown experimentally. Therefore, this study aimed to experimentally examine the mood repair effect of positive involuntary autobiographical memory among Japanese adults. After a pilot study to select cue words, we examined whether positive involuntary autobiographical memory retrieval could improve negative mood. As a result, mood improvement was enhanced by positive memory being recalled involuntarily, while mood improvement was shown with and without the retrieval of the positive involuntary autobiographical memory. Therefore, the mood repair effect by positive IAM was shown even after preventing the influence of the emotional valence of retrieval cues. From these results, the mood repair effect of positive involuntary autobiographical memory retrieval was experimentally demonstrated among Japanese adults.